Pengaruh Content Marketing, Physical Evidence, dan Word of Mouth Terhadap Keputusan Pembelian - Nurul Apriyana; Restu Frida Utami; Herni Justiana Astuti; Hermin Endratno (Forum Kerjasama Pendidikan Tinggi, 2026)
The increasingly fierce competition in the food and beverage industry in Purwokerto City requires cafe business owners to understand the dominant factors that trigger consumer purchasing decisions. This study aims to analyze the influence of content marketing, physical evidence, and word of mouth on purchasing decisions among customers of Arasta Alpha Cafe in Purwokerto. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis method. The sample in this study consisted of 127 respondents selected using a purposive sampling technique based on certain criteria. The results of the analysis show that content marketing and physical evidence have a positive and significant effect on purchasing decisions. Conversely, word of mouth does not have a significant effect on purchasing decisions. The three variables are able to explain 71.4% of the variation in consumer purchasing decisions. This finding indicates that the model built has strong predictive power in explaining consumer behavior. This emphasizes the importance of implementing relevant content marketing strategies and optimal physical evidence in attracting purchasing decisions. The results show that word of mouth has no significant effect, indicating that verbal recommendations without visual evidence are less able to validate consumer expectations. On the other hand, content marketing and visible physical evidence play a greater role in influencing purchasing decisions.